An image-invariant neural response to familiar faces in the human medial temporal lobe. (November 2016) - Weibert, Katja; Harris, Richard J.; Mitchell, Alexandra; Byrne, Hollie; Young, Andrew W.; Andrews, Timothy J.
Abstract: The ability to recognise familiar faces with ease across different viewing conditions contrasts with the inherent difficulty in the perception of unfamiliar faces across similar image manipulations. Models of face processing suggest that this difference is based on the neural representation for familiar faces being more invariant to changes in the image, than it is for unfamiliar faces. Here, we used an fMR-adaptation paradigm to investigate neural correlates of image-invariant face recognition in face-selective regions of the human brain. Participants viewed faces presented in a blocked design. Each block contained different images of the same identity or different images from different identities. Faces in each block were either familiar or unfamiliar to the participants. First, we defined face-selective regions by comparing the response to faces with the response to scenes and scrambled faces. Next, we asked whether any of these face-selective regions showed image-invariant adaptation to the identity of a face. The core face-selective regions showed image-invariant adaptation to familiar and unfamiliar faces. However, there was no difference in the adaptation to familiar compared to unfamiliar faces. In contrast, image-invariant adaptation for familiar faces, but not for unfamiliar faces, was found in face-selective regions of the medial temporal lobe (MTL). Taken together, our results suggest that the marked differences in the perception of familiar and unfamiliar faces may depend critically on neural processes in the medial temporal lobe.